2013
DOI: 10.1016/j.jaubas.2012.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Radioactivity of long lived gamma emitters in rice consumed in Kuwait

Abstract: A study of long-lived gamma emitting radionuclides in rice consumed in Kuwait was performed. The study targeted the natural radionuclides 238 U, 232 Th, and 40 K, in addition to the anthropogenic radionuclide 137 Cs. Annual effective doses from rice consumption were estimated to be 33 and 60 lSv for the adult and child age groups respectively. These values were found to be of several orders of magnitude less than the 0.29 mSv year À1 world average of the ingestion exposure from natural sources reported in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 6 publications
0
6
0
1
Order By: Relevance
“…They are made from a combination of flour, shortening, leavening, and milk or water. Studies worldwide have investigated natural radionuclides in food consumed in different parts of the world (1,2,7,8,11,16). The Fukushima nuclear accident has raised much concern about contaminated foods.…”
mentioning
confidence: 99%
“…They are made from a combination of flour, shortening, leavening, and milk or water. Studies worldwide have investigated natural radionuclides in food consumed in different parts of the world (1,2,7,8,11,16). The Fukushima nuclear accident has raised much concern about contaminated foods.…”
mentioning
confidence: 99%
“…The levels of background and the detection limits of technique may conceal minor peaks of 238 U, 232 Th [27]. Previous studies reported that the detection of 238 U and 232 Th is not necessary to be found in all food samples [28,29]. The existence of 137 Cs in water samples may because of the Chernobyl accident fallout, the usage of contaminated water bottles [8].…”
Section: Resultsmentioning
confidence: 99%
“…Doğal ve yapay radyonüklitlerin yiyecekler yoluyla da insanlara geçtiği göz önüne alınarak yiyecekler içinde bulanan doğal ve yapay radyonüklitlerin aktivite konsantrasyonlarını belirlemek amacıyla da çalışmalar yapılmıştır. Örneğin; bal [15], süt [5,16], marketlerde satılan çeşitli yiyecekler [17], balık [18], gıda maddeleri (sebze, tahıl ve meyve) [19] doğal ve yapay radyonüklitlerin aktivite konsantrasyonları incelenen örneklerden bazılardır. Ülkemizde de doğal ve yapay radyonüklitlerin aktivite konsantrasyonlarını belirlemek amacıyla kum [20,21], toprak [22,23], kaya [24], sediment [25,26], gıda maddeleri [27,28,29,30] incelenmiştir.…”
Section: Gi̇ri̇ş (Introduction)unclassified